A randomised controlled feasibility trial of family and social network intervention for young people who misuse alcohol and drugs: study protocol (Y-SBNT). Issue 1 (December 2015) - Watson, Judith; Back, Donna; Toner, Paul; Lloyd, Charlie; Day, Ed; Brady, Louca-Mai; Templeton, Lorna; Ambegaokar, Sangeeta; Parrott, Steve; Torgerson, David; Cocks, Kim; Gilvarry, Eilish; et al.
Abstract Background A growing body of research has identified family interventions to be effective in treating young people's substance use problems. However, despite this evidence, take-up of family-based approaches in the UK has been low. Key factors for this appear to include the resource-intensive nature of most family interventions which challenges implementation and delivery in many service settings and the cultural adaptation of approaches developed in the USA to a UK setting. This study aims to demonstrate the feasibility of recruiting young people to a specifically developed family- and wider social network-based intervention by testing an adapted version of adult social behaviour and network therapy (SBNT). Methods A pragmatic, randomised controlled, open feasibility trial delivered in two services for young people in the UK. Potential participants are aged 12–18 years referred for drug or alcohol problems to either service. The main purpose of this study is to demonstrate the feasibility of recruiting young people to a specifically developed family and social network-based intervention. The feasibility and acceptability of this intervention will be measured by recruitment rates, treatment retention, follow-up rates and qualitative interviews. The feasibility of training staff from existing services to deliver this intervention will be explored. Using this opportunity to compare the effectiveness of the intervention against treatment as usual, Timeline Follow-Back interviews will document the proportion of days on which the main problem substance was used in the preceding 90-day period at each assessment point. The economic component will examine the feasibility of conducting a full incremental cost-effectiveness analysis of the two treatments. The study will also explore and develop models of patient and public involvement which support the involvement of young people in a study of this nature. Discussion An earlier phase of work adapted social behaviour and network therapy (adult approach) to produce a purpose-designed youth version supported by a therapy manual and associated resources. This was achieved by consultation with young people with experience of services and professionals working in services for young people. This feasibility trial alongside ongoing consultations with young people will offer a meaningful understanding of processes of delivery and implementation. Trial registration ISRCTN93446265 ; Date ISRCTN assigned 31/05/2013.